Functionalized graphene aerogel composites for high-performance asymmetric supercapacitors. (January 2015) - Yu, Zenan; McInnis, Matthew; Calderon, Jean; Seal, Sudipta; Zhai, Lei; Thomas, Jayan
Abstract: Asymmetric supercapacitors (ASCs) have played a leading role in realizing energy storage devices with high energy and power densities. While both anode and cathode materials are important for high performance ASCs, more research effort has been devoted to developing cathode materials because the energy source of an ASC is mostly attributed to the cathode. However, the development of anode materials is essential in order to achieve high power density as well as stable long-term cycle life of ASCs. In this study, functionalized graphene aerogel (GA) decorated with palladium (Pd) nanoparticles is used as an efficient ASC anode material. The high surface area (328 m 2  g −1 ) and low electrical resistivity (50 times lower than one without Pd) of the GA composite grants a high specific capacitance (175.8 F g −1 at 5 mV s −1 ), excllent rate capability (48.3% retention after a 10 fold increase of scan rate), and remarkable reversibility. ASCs assembled from manganese dioxide (cathode) and GA composite (anode) show stable extended cell voltage, fast charge–discharge capability, excellent cycle stability (89.6% retention after 3000 cycles), and high energy and power densities (average of 13.9 W h kg −1 and 13.3 kW kg −1 ). These results demonstrate the great potential of the GA composite as an efficient anode material for high performance energy storage devices. Graphical abstract: Highlights: A novel method which enables palladium (Pd) nanoparticles to be conformally loaded onto graphene aerogel (GA) was successfully developed. 50 times decrease of electrical resistivity of GA was achieved after Pd loading. Pd loaded GA (P-GA) composite grants high surface area, stable negative voltage window, and high specific capacitance (175.8 F g −1 ). The first demonstration of using P-GA composite as anode for high-performance asymmetric supercapacitor.